Treatment of self‐injurious behavior using differential punishment of high rates of behavior (DPH). (10th April 2017) - Manente, Christopher J.; LaRue, Robert H.
Abstract : The purpose of the current investigation was to explore the effectiveness of differential punishment of high rates of behavior (DPH) to treat the severe self‐injury of a 28‐year‐old man with autism in an adult day program setting. DPH procedures involve the use of an established criterion related to a rate of responding within some time interval at which a punisher is delivered. The implementation of DPH in this study resulted in a substantial long‐term reduction of severe self‐injurious behavior. These findings are significant in that they provide a model for the design and implementation of punishment procedures that can be adopted in applied settings where staff resources are limited. The results of this study have implications for the treatment of severe problem behavior among individuals with autism across settings and age groups.